2023
DOI: 10.3390/su15086510
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Strain as Biological Tool to Remove Genotoxicity Effect of Phenolic Compounds from Olive Mill Wastewater

Abstract: This study aims to select fungi isolates to reduce olive mill wastewater (OMWW) chemical oxygen demand (COD) and phenolic compounds (PC), as well as their genotoxicity effect. Treatment with mold, isolated by an innovative technique using phenolic compound-selective media, showed a reduction rate of about 4% for COD and 2% for PC during one month of incubation without optimization of the treatment conditions. Whereas this percentage reached 98% and 96% for COD and PC, respectively, after only 12 days of treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Thus, we could say that indeed OMW are among the most dangerous industrial liquids discharges, as reported other authors in the literature [20]. Thus, given their high pollutant load, these liquids waste pose multiple environmental problems when released into the environment without prior treatment [21]. Hence, the need to find effective, practical, and immediate solutions to this environmental scourge.…”
Section: Introductionmentioning
confidence: 52%
“…Thus, we could say that indeed OMW are among the most dangerous industrial liquids discharges, as reported other authors in the literature [20]. Thus, given their high pollutant load, these liquids waste pose multiple environmental problems when released into the environment without prior treatment [21]. Hence, the need to find effective, practical, and immediate solutions to this environmental scourge.…”
Section: Introductionmentioning
confidence: 52%
“…The activity of the Laccase (1,063 ± 26 U/L) of fungi causing the disease white rot ( Phanerochaete chrysosporium, Pycnoporus cinnabarinus, Ceriporiopsis subvermispora, and Trametes pubescens ) removed 87–92% of phenolic materials at pH 5.0 ( Robinson et al, 2001 ; Strong, 2010 ). Laccase fungi hydrolyzed the winery wastewater and potentially removed the phenolic compounds, color, and COD ( Strong and Burgess, 2008 ; Boutafda et al, 2023 ). The renowned fungal species Pleurotus ostreatus and T. versicolor , which are known for their ability to produce laccase, generate energy via the enzymatic layer located within the fungi’s cathode electrode ( Mani and Hameed, 2019 ).…”
Section: Fungal Catalytic Role In Fcsmentioning
confidence: 99%
“…In recent years, there has been a growing interest in exploring the potential of OMW as a valuable source of bioactive compounds (Boutafda et al, 2023). Polyphenols, in particular, have garnered significant attention due to their reported health benefits (Rathod et al, 2023).…”
Section: Introductionmentioning
confidence: 99%